2019
DOI: 10.1038/s41598-019-53562-y
|View full text |Cite|
|
Sign up to set email alerts
|

Ultra high dose rate (35 Gy/sec) radiation does not spare the normal tissue in cardiac and splenic models of lymphopenia and gastrointestinal syndrome

Abstract: Recent reports have shown that very high dose rate radiation (35–100 Gy/second) referred to as FLASH tends to spare the normal tissues while retaining the therapeutic effect on tumor. We undertook a series of experiments to assess if ultra-high dose rate of 35 Gy/second can spare the immune system in models of radiation induced lymphopenia. We compared the tumoricidal potency of ultra-high dose rate and conventional dose rate radiation using a classical clonogenic assay in murine pancreatic cancer cell lines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 32 publications
2
83
0
Order By: Relevance
“…This relationship is important to consider when examining studies such as those by Favaudon et al (10), and Vozenin et al (15,16), which used 40-60 and 300 Gy/s, respectively when administering FLASH-RT. In contrast to previously mentioned studies, a recent interesting study by Venkatesulu et al showed a higher toxicity for FLASH-RT delivered at 35 Gy/s than for CONV-RT delivered at 0.1 Gy/s (33). This dose rate is probably on the low side for a sparing effect to occur but that does not explain the highly unexpected increased toxicity they found for FLASH-RT in all of their experiments, especially the increased toxicity of a factor 1.3-1.4 for their in vitro data.…”
Section: What Factors Influence the Flash Effect?mentioning
confidence: 67%
See 2 more Smart Citations
“…This relationship is important to consider when examining studies such as those by Favaudon et al (10), and Vozenin et al (15,16), which used 40-60 and 300 Gy/s, respectively when administering FLASH-RT. In contrast to previously mentioned studies, a recent interesting study by Venkatesulu et al showed a higher toxicity for FLASH-RT delivered at 35 Gy/s than for CONV-RT delivered at 0.1 Gy/s (33). This dose rate is probably on the low side for a sparing effect to occur but that does not explain the highly unexpected increased toxicity they found for FLASH-RT in all of their experiments, especially the increased toxicity of a factor 1.3-1.4 for their in vitro data.…”
Section: What Factors Influence the Flash Effect?mentioning
confidence: 67%
“…Many pre-clinical studies have reported a successful FLASH normal tissue sparing effect, but it cannot be overlooked that there have also been several studies reporting no significant sparing of normal tissues following irradiation at ultra-high dose rates (29)(30)(31)(32)(33). For example, Smyth et al delivered whole and partial body (abdominal or head) synchrotron irradiation to mice, at ultra-high dose rates of 37-41 Gy/s in the hope of characterizing the equivalent CONV-RT dose (32).…”
Section: Flash-rt Limits Normal Tissue Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…FLASH-RT may directly affect immune cells or indirectly influence the tumor microenvironment. Some evidence suggests that immune cells are not preferentially spared by ultra-high dose rates similar to FLASH [106]. TGF-β is a master regulator of immune homeostasis following RT, largely mediating immunosuppressive effects.…”
Section: Radiotherapy and Immune Signalingmentioning
confidence: 99%
“…Electrons 10,13,15,[19][20][21][25][26][27][28] , kilo-voltage (keV) X-rays 18,29 and proton [30][31][32] have been utilized in FLASH preclinical research; however, those modalities are not ideal in clinical application. Electrons and keV X-rays are usually used to treat superficial tumor sites, but not suitable for tumors in the deep body, such as lung cancer, breast cancer, colorectal cancer, prostate cancer, due to their limited penetration powers.…”
Section: Introductionmentioning
confidence: 99%